Forecast of Revenue and Expenditure for the Annual Plan 1981-82 (Revised) and 1982-83 Government of Haryana - Planning Commission (Planning Commission, 1981)
This forecast of revenue receipts, revenue expenditure and capital receipts during the current financial year and 1982-83 has been prepared keeping in view the recommendations made by the 7th Finance Commission. Some departures from these recommendations have been made wherever the trend of the receipts and expenditure and fresh expenditures sanctioned after the Budget Estimates 1981-82 so warranted.
Government of Haryana, Finance Department (Resources Cell)